ANALISIS PENYELESAIAN SENGKETA E ANALISIS PENYELESAIAN SENGKETA EKONOMI SAWIT: KETIMPANGAN HARGA PETANI DAN HARGA EKSPOR DI KALIMANTAN TENGAH - Wasilaturohmah (JSE: Jurnal Sharia Economica, 2026)
This study analyzes the economic dispute in the palm oil sector concerning the price disparity between smallholder farmers and export markets in Central Kalimantan. Palm oil, as one of Indonesia’s main export commodities, significantly contributes to national income but also presents persistent inequality in its value chain. Farmers often receive low Fresh Fruit Bunch (FFB) prices due to dependence on middlemen, lack of land legality and institutional capacity, poor FFB quality, inconsistent government regulations, and limited market information. The research employs a qualitative descriptive approach with a case study design supported by a normative Islamic economic perspective emphasizing justice (‘adl), benefit (maslahah), and the prohibition of injustice (dzulm). Data were collected through interviews with farmers and relevant stakeholders, as well as secondary sources such as official reports and literature reviews. The results reveal that structural imbalances in price distribution and weak bargaining power of farmers lead to social and economic inequality. From the perspective of Islamic economics, these practices reflect elements of monopoly (ihtikar), fraud (ghishsh), and uncertainty (gharar), all of which contradict the principles of justice and transparency. Therefore, dispute resolution should prioritize non-litigation methods such as conciliation (al-sulh) and arbitration (tahkim) under Islamic arbitration bodies like Basyarnas. Moreover, the implementation of transparent and fair trade contracts—such as Salam and Istishna’—and government intervention based on maslahahare necessary to ensure equitable price mechanisms and improve the welfare of palm oil farmers sustainably.